Implementation of communication routines facilitating person‐centred care in long‐term residential care: A pilot study. (23rd September 2022) - Forsgren, Emma; Saldert, Charlotta
Abstract: Background: Specific routines such as the development of personal communication plans can improve the interaction between people with communication disorders and healthcare staff. Objective : This pilot study explores a model for implementing communication routines including personal communication plans in long‐term residential care. Design, Setting and Participants: This multiple case study includes two residential care facilities that differ in size and the number of languages spoken. Intervention or main variables studied implementation strategies involved workshops, individual coaching and follow‐up visits. Main outcome measure implementation was assessed using goal attainment measurements, and the staff's views about facilitators and barriers to implementation were explored through structured interviews using the Theoretical Domains Framework. Results: The overall implementation success rate for the facilities was moderate, and one of the facilities showed promising results related to personal communication plans. Both facilities experienced barriers to implementation, including management problems and a lack of reminders. However, the two facilities seem to have different motivations for change. Discussion and Conclusions: Regardless of the features of the facility, successful implementation requires stable and committed leadership. Moreover, experiences with language diversity may motivate staff to implement communication routines. Patient or Public Contribution: The content of the implementation model used (i.e., choice of specific routines and implementation strategies) was coproduced by staff, managers and the researchers involved in this project. The staff and managers were responsible for the implementation of the new routines under the supervision of the researchers.